STUDI SISTEM INJEKSI INHIBITOR KOROSI TERHADAP KANDUNGAN ORTHOFOSFAT DAN SENG SEBAGAI PARAMETER KENDALI KOROSI PADA SISTEM PENDINGIN SEKUNDER RSG-GAS - Edwin Rizki Safitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2017)
Reaktor Serba Guna G.A Siwabessy (RSG-GAS) was built since 1983. RSG-GAS is a type of research reactor equipped with heat carrier and cooling system which serves to remove heat arising from fission reactions. In the heat carrier medium, the reactor equipped with a secondary cooling system using water originating from PAM Puspiptek. Water used in secondary cooling systems can cause some major problems of crust, corrosion, and moss or microorganisms. In this research, the phosphorus (orthophosphate), zinc, and conductivity and pH in the secondary cooling system have been measured to determine whether or not the flow rate of the injection system is used. Determination of concentration of the elements was performed using a DR / 2400 spectrophotometer portable device with ZincoVer 5 Powder Pillow reagent, cyclohexane for zinc concentration, and PhosVer 3 phophate for phosphorus concentration. From the results obtained, the overall flow rate of injector injection of 1.7 L / h gives a good result. Significant differences occurred only in conductivity values ​​dated July 21, 2009 both in piped water and cooling towers exceeding 950 μs / cm. And the value of orthophosphate concentration dated August 4, 2009 that exceeds 10 ppm.